Transurethral Vaporization of Bladder Neck Using Holmium Laser: First Experience in Manado - Mahesa Krishna; Eko Arianto; Ari Astram; Frendy Wihono; Christof Toreh (Medical Scope Journal, 2024)
Abstract: Bladder neck contracture (BNC) is a potential complication after radical prostatectomy (RP). This may be a result of inadequate approximation at the time of surgery, urinary extravasation, or distraction of the bladder neck from a hematoma. Patients commonly complains of a poor urinary stream or prolonged unexplained incontinence. Treatment of BNC requires a tailored approach and can range from simple, office-based procedures to complex surgical reconstruction. We reported a case of 81-year-old male complaining urine retention for one month. The patient had previous open prostate procedure a year prior. On examination, neurogenic causes were excluded. Retrograde ureterocystography revealed bladder neck contracture. Patient was diagnosed as bladder neck contracture post open prostatectomy surgery. Transurethral holmium laser vaporization with 800 micrometre, 20 Hz frequency and 4,5 Joule of power. through a ureteroscope was performed. Two-way Folley catheter 18Fr was inserted without irrigation. Patient was discharged post-surgery two days after catheter removal and spontaneous micturition. Endoscopic balloon dilatation with incision appears to offers promising result in the management of BNC. The consideration of using transurethral vaporization with holmium laser modality was the first procedure ever done in Manado. In conclusion, TUVP is one of the alternatives, minimally invasive procedures to treat BNC. The use of holmium laser for the incision of bladder neck is another alternative to treat BNC with great outome proven by the length of stay (LOS) of two days after the procedure was done. Keywords: bladder neck contracture; transurethral vaporization; holmium laser; post prostatectomy